Error and Mathematics Anxiety Analysis of Junior High School Students in Completing Diagnostic Tests - Soewardini, Herfa Maulina Dewi; Fuad, Yusuf; Ekawati, Rooselyna; Murdiana, Tri D. (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2023)
This study aims to analyze the math anxiety and wrong answers of junior high school students. As many as 11 female students and 5 male students from class VIID SMPN in Surabaya voluntarily participated in the diagnostic test during the Covid-19 pandemic. The test consists of 15 multiple choice questions and 5 description questions, carried out online with Google Meet and video on-cam, followed by structured interviews via Google Forms. The test results showed that 4 students (25%) fulfilled the KKM score and 12 students (75%) still lacked the KKM. Using the Newman error procedure, the average component of student errors was: reading (16.55%), comprehension (17.24%) ), transformation (22.07%), process skills (21.38%), and coding (22.76%) The results of the diagnosis confirmed that the factors that influence students' math anxiety are the easily nervous attitude that is routine in tests (31 .25%), nervous (37.5%), confused (56.25%), forgot the formula in multiple-choice questions (37.5%) and description questions (87.5%), and still need help from the teacher ( 37.5%), parents (75%), or peers (87.5%).Penelitian ini bertujuan menganalisis kecemasan matematika dan kesalahan jawaban dari siswa SMP. Sebanyak 11 siswa perempuan dan 5 siswa laki-laki dari kelas VIID SMPN di Surabaya secara sukarela berpartisipasi dalam tes diagnostik di masa pandemi Covid-19. Tes terdiri dari 15 soal pilihan ganda dan 5 soal uraian, dilaksanakan secara daring dengan Google meet dan video on-cam, serta dilanjutkan wawancara terstruktur melalui Google forms. Hasil tes adalah 4 siswa (25%) memenuhi skor (KKM dan 12 siswa (75%) masih kurang dari KKM. Dengan prosedur kesalahan Newman, rerata komponen kesalahan siswa adalah: membaca (16,55%), pemahaman (17,24%), transformasi (22,07%), keterampilan proses (21,38%), dan pengkodean (22,76%). Hasil diagnosa menegaskan bahwa faktor-faktor yang mempengaruhi kecemasan matematika siswa adalah sikap mudah grogi yang rutin dalam tes (31,25%), nervous (37,5%), bingung (56,25%), lupa rumus pada soal pilihan ganda (37,5 %) maupun soal uraian (87,5%), serta masih perlu bantuan dari guru (37,5%), orangtua (75%), atau teman sebaya (87,5%).